Dual Targeting of G9a and DNA Methyltransferase‐1 for the Treatment of Experimental Cholangiocarcinoma. Issue 6 (18th June 2021) - Colyn, Leticia; Bárcena‐Varela, Marina; Álvarez‐Sola, Gloria; Latasa, M. Ujue; Uriarte, Iker; Santamaría, Eva; Herranz, Jose M.; Santos‐Laso, Alvaro; Arechederra, Maria; Ruiz de Gauna, Mikel; Aspichueta, Patricia; Canale, Matteo; et al.
Abstract : Background and Aims: Cholangiocarcinoma (CCA) is a devastating disease often detected at advanced stages when surgery cannot be performed. Conventional and targeted systemic therapies perform poorly, and therefore effective drugs are urgently needed. Different epigenetic modifications occur in CCA and contribute to malignancy. Targeting epigenetic mechanisms may thus open therapeutic opportunities. However, modifications such as DNA and histone methylation often coexist and cooperate in carcinogenesis. We tested the therapeutic efficacy and mechanism of action of a class of dual G9a histone‐methyltransferase and DNA‐methyltransferase 1 (DNMT1) inhibitors. Approach and Results: Expression of G9a, DNMT1, and their molecular adaptor, ubiquitin‐like with PHD and RING finger domains‐1 ( UHRF1 ), was determined in human CCA. We evaluated the effect of individual and combined pharmacological inhibition of G9a and DNMT1 on CCA cell growth. Our lead G9a/DNMT1 inhibitor, CM272, was tested in human CCA cells, patient‐derived tumoroids and xenograft, and a mouse model of cholangiocarcinogenesis with hepatocellular deletion of c‐Jun‐N‐terminal‐kinase (Jnk)‐1/2 and diethyl‐nitrosamine (DEN) plus CCl4 treatment (Jnk Δhepa + DEN + CCl4 mice). We found an increased and correlative expression of G9a, DNMT1, and UHRF1 in CCAs. Cotreatment with independent pharmacological inhibitors G9a and DNMT1 synergistically inhibited CCA cell growth. CM272 markedly reduced CCA cell proliferation and synergized with Cisplatin and the ERBB‐targeted inhibitor, Lapatinib. CM272 inhibited CCA tumoroids and xenograft growth and significantly antagonized CCA progression in Jnk Δhepa + DEN + CCl4 mice without apparent toxicity. Mechanistically, CM272 reprogrammed the tumoral metabolic transcriptome and phenotype toward a differentiated and quiescent status. Conclusions: Dual targeting of G9a and DNMT1 with epigenetic small molecule inhibitors such as CM272 is a potential strategy to treat CCA and/or enhance the efficacy of other systemic therapies.